PENGARUH KEADILAN PAJAK, KUALITAS PELAYANAN PAJAK, KEMUNGKINAN TERDETEKSINYA KECURANGAN, SANKSI PERPAJAKAN, DAN TARIF PAJAK TERHADAP PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK - Christina Vionita; Vince Ratnawati; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of tax fairness, quality of tax service, probability of fraud detection, tax sanction, and tax rates against the taxpayer’s perceptions about tax evasion. The population in this study is the micro, small, and medium business entrepreneurs taxpayer in Pekanbaru and listed on KPP Pratama Senapelan Pekanbaru. The sampling technique using convenience sampling method nad determination of sampel size in this study was calculated by formula slovin obtained by 100 respondents. The data of this research using primary data directly through a questionnaires and analyzed using SPSS 17. The data were analyzed to test the hypothesis using multiple linear regression analsys approach. The result of this study showed that tax fairness, quality of tax service, probability of fraud detection, and tax sanction have effect on taxpayer’s perceptions about tax evasion. While the tax rates has no effect regarding on taxpayer’s perceptions about tax evasion.Keywords: tax fairness, quality of tax service, tax sanction, tax rates, and tax evasion